(untitled) (International Journal of Economics Development Research (IJEDR), 2025)
The purpose of this study was to analyze the effect of understanding the Tri Pantangan teachings and understanding tax regulations on taxpayer compliance in Yogyakarta. This study employed a quantitative approach with a population consisting of all registered taxpayers in Yogyakarta. The sample was selected using purposive sampling to ensure that the respondents met the research criteria. Data were collected through questionnaires distributed to taxpayers. The findings indicate that understanding the Tri Pantangan teachings does not significantly influence taxpayer compliance. In contrast, understanding tax regulations has a positive and significant effect on taxpayer compliance. These results highlight the importance of tax knowledge in shaping taxpayer behavior. This study provides practical contributions for the Directorate General of Taxes in designing strategies to enhance taxpayer compliance and serves as a reference for future research on factors influencing taxpayer compliance in Indonesia. Furthermore, the findings can assist tax authorities in developing more effective and evidence-based policies to promote compliance.